الدراسة المقارنة عن كفاءة الترجمة من اللغة العربية إلى الإندونيسية - Azhari, Saefullah; Nu’man, Muhammad; Jamilah, Mimi; Lakbatun, Mirna; Rifqiyah, Nur Alfin Nafidzatur (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Translation is not just comparing words with each other, but the equivalence and arrangement of the pairs of the two languages. There is no need to know the meaning of the whole expression. Translation from one sign to another, and this translation means the transfer of messages from one type of symbolic system to another without being accompanied by verbal signs, so that everyone can understand it. In this research, the researcher wants to discuss about. How is the efficiency of translation from Arabic to Indonesian for Intensive Arabic students at the Al Noor Institute for Surabaya Students. How is the efficiency of translation from Indonesian to Arabic for Intensive Arabic students at “The Light” Institute for Students in Surabaya. How would you compare the efficiency of translation from Arabic to Indonesian and From Indonesian to Arabic for Arabic intensive students at the “Al-Nour” Institute for students in Surabaya?